Afro-surrealism in theatre making: an exploration of how Afro-Surrealism can influence the making of the South African play Ngilande (2019) written, directed and performed by Sizwe Hlophe - Hlophe, Nelson Sizwe (My University, 2021)
This research report conducts an exploration of Afro-Surrealism’s influence in the making of the South African play, Ngilande (2019). This research is motivated by a desire and interest in developing an African aesthetic for theatre. This is to expand the notions of performance beyond what has been learned at academic institutions (Eurocentric approaches). This research enquiry makes use of qualitative research methods; primary and secondary data; and a Practice-Based research approach. This approach offers the necessary critical analyses of the creative application that is informed by Afro-Surrealism, African centred ideologies and performance practices. Afro-Surrealism exhibits similarities to other African centred ideologies and performance practices. The first similarity worth noting is the invisible made visible. Afro-Surrealism uses it to expose and interrogate hidden truths, and for African cosmology it is truth. Afro-Surrealism creates the link for making the invisible visible through the Marvelous. The Marvelous explores power and ideasthrough methods that transcend reality by including dreams, religion, mythology and the supernatural. For the African that sees the world through an African Cosmological lens, The Marvelous is reality, as evident in rituals such as ukuLanda. African Cosmology encapsulates religion, mythology, the supernatural and dreams as extended platforms for spiritual engagements. Both Afro-Surrealism and African Cosmology place a sense of duty to the uncovering of the invisible. Ngilande (2019) is the symbolic manifestation of the ukuLanda ritual. It attempts to reclaim a Black pride and Black identity that has been systematically killed by hegemonic power structures
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Theatre and Performance to the Faculty of Humanities, School of Arts, University of the Witwatersrand, 2021